2023
DOI: 10.3389/fmicb.2022.1085918
|View full text |Cite
|
Sign up to set email alerts
|

Polar protein Wag31 both activates and inhibits cell wall metabolism at the poles and septum

Abstract: Mycobacterial cell elongation occurs at the cell poles; however, it is not clear how cell wall insertion is restricted to the pole or how it is organized. Wag31 is a pole-localized cytoplasmic protein that is essential for polar growth, but its molecular function has not been described. In this study we used alanine scanning mutagenesis to identify Wag31 residues involved in cell morphogenesis. Our data show that Wag31 helps to control proper septation as well as new and old pole elongation. We have identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 69 publications
(107 reference statements)
0
7
0
Order By: Relevance
“…However, our data indicate that polar localization of MmpL3 does not correlate with polar growth, as the wag31 K20A mutant is defective in old pole elongation (28) but has increased old pole localization of MmpL3, while the L34A mutant is defective in new pole elongation and has decreased new pole localization of MmpL3.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…However, our data indicate that polar localization of MmpL3 does not correlate with polar growth, as the wag31 K20A mutant is defective in old pole elongation (28) but has increased old pole localization of MmpL3, while the L34A mutant is defective in new pole elongation and has decreased new pole localization of MmpL3.…”
Section: Resultsmentioning
confidence: 58%
“…In an effort to better understand the molecular function of Wag31, we looked for factors that were genetically linked to wag31 by conducting a suppressor screen. We had previously generated a number of wag31 partial loss of function point mutants (28). We passaged several slow-growing wag31 point mutants - D7A, K20A, and L34A - for several days, struck them out regularly and looked for large colony mutants.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that the ability of M. smegmatis to recover from benzyl alcohol depends at least in part on its ability to reform the IMD, and therefore, that genes that promote membrane partitioning would constitute a subset of the genes that enable M. smegmatis to tolerate and/or recover from benzyl alcohol. In mycobacteria, the essential, tropomyosin-like protein Wag31 (DivIVA) promotes polar cell wall assembly and rod shape and promotes IMD protein localization and isolability ( García-Heredia et al, 2018 ; Habibi Arejan et al, 2022 ; Jani et al, 2010 ; Kang et al, 2008 ; Melzer et al, 2018 ). While DivIVA depletion slowed M. smegmatis growth, as expected, we observed only a small additional growth defect when bacteria were exposed to benzyl alcohol ( Figure 2—figure supplement 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…DivIVA was shown to control the activity of the enzymes involved in the cell wall synthesis ( 25 , 26 ). At the latest stages of cell division, DivIVA is recruited to the division site where it interacts with divisome protein PBP3 ( 27 , 28 ). It was also suggested that the other DivIVA interaction partners CwsA and CrgA may contribute to DivIVA relocation ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…The late recruitment of DivIVA at the cell division site suggests its involvement in constituting the new cell poles ( 11 , 19 ). DivIVA mutational analysis suggested that DivIVA activity involves different interactions at the new pole, the old pole, and the septum ( 27 ). However, the details of the DivIVA role in the formation of the new poles are still to be investigated.…”
Section: Introductionmentioning
confidence: 99%